Divided Politics, Divided Nation : Hyperconflict in the Trump Era - West, Darrell M., 1954- (Book collections on Project MUSE., 2019)
"Why are Americans so angry with each other? The United States is caught in a partisan hyperconflict that divides politicians, communities, and even families. Politicians from the president to state and local office-holders play to strongly-held beliefs and sometimes even pour fuel on the resulting inferno. This polarization has become so intense that many people no longer trust anyone from a differing perspective. Drawing on his personal story of growing up as a fundamentalist Christian on a dairy farm in rural Ohio, then as an academic in the heart of the liberal East Coast establishment, Darrell West analyzes the economic, cultural, and political aspects of polarization. He takes advantage of his experiences inside both conservative and liberal camps to explain the views of each side and offer insights into why each is angry with the other. West argues that societal tensions have metastasized into a dangerous tribalism that seriously threatens U.S. democracy. Unless people can bridge these divisions and forge a new path forward, it will be impossible to work together, maintain a functioning democracy, and solve the country's pressing policy problems"--Publisher's description.